2008
DOI: 10.1016/j.jorganchem.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis, structures, and electrochemistry of 1′-heteroaryl-2,5-dimethylazaferrocenes

Abstract: a b s t r a c tWe report the synthesis of 1 0 -heteroaryl-2,5-dimethylazaferrocenes (heteroaryl = 2-bromothiophen-5-yl and 2-bromopyrid-6-yl) via palladium catalysed cross-coupling reactions along with their crystallographically determined structures. The newly synthesized compounds as well as the parent 2,5-dimethylazaferrocene have been investigated by cyclic voltammetry (CV) and were found to exhibit reversible first oxidations followed by an irreversible oxidation at considerably higher potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(47 reference statements)
3
11
0
Order By: Relevance
“…Based on this methodology, complexes 1, 2, 3, 6, 7 and 9 have been obtained [4][5][6][7]. We have already reported that 2,5-dimethylazaferrocenylzinc chloride undergoes palladium catalyzed cross-coupling reactions with dibromoheteroarenes to yield 1 0 -heteroaryl-2,5-dimethylazaferrocenes [13]. As a logical continuation of this study we applied this type of cross-coupling reactions toward the preparation of symmetrical heteroaryl bridged dinuclear azaferrocenyl complexes.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Based on this methodology, complexes 1, 2, 3, 6, 7 and 9 have been obtained [4][5][6][7]. We have already reported that 2,5-dimethylazaferrocenylzinc chloride undergoes palladium catalyzed cross-coupling reactions with dibromoheteroarenes to yield 1 0 -heteroaryl-2,5-dimethylazaferrocenes [13]. As a logical continuation of this study we applied this type of cross-coupling reactions toward the preparation of symmetrical heteroaryl bridged dinuclear azaferrocenyl complexes.…”
Section: Resultsmentioning
confidence: 88%
“…In the next step a catalytic amount of PdCl 2 (PPh 3 ) 2 in THF and the appropriate reactive 1 0 -heteroaryl-2,5-dimethylazaferrocenes 16 [13], 17 [13] or 18 were successively added at room temperature to the stirring reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations